A COMPREHENSIVE EXAMINATION OF THE IMPACT OF A DIGITAL MARKETING CAMPAIGN ON CONSUMER ENGAGEMENT IN E-COMMERCE - Listian Indriyani Achmad; Henny Noviany; Eloh Bahiroh; Sri Ndaru Arthawati; Abdul Rosid (CV. Adiba Aisha Amira, 2025)
This study thoroughly investigates the transformative effects of a digital marketing campaign on consumer engagement within the e-commerce domain. Employing a mixed-methods approach, the research combines quantitative analyses of engagement metrics with qualitative insights gathered through in- depth interviews. The campaign's impact on click-through rates, conversion rates, and demographic variations in engagement levels is meticulously scrutinized, providing a nuanced understanding of its effectiveness. Qualitative findings reveal the enduring influence of the campaign on brand perception and consumer loyalty, emphasizing the significance of narrative elements in digital marketing. The implications for businesses are profound, advocating for a localized and narrative-driven approach to optimize digital strategies. Despite acknowledging study limitations, including a focus on a specific campaign and reliance on self- reported data, this research contributes valuable insights into the dynamic interplay between digital campaigns and consumer behavior in the ever-evolving landscape of e-commerce.